THE INFLUENCE OF WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT THE HEALTH OFFICE OF SIDENRENG RAPPANG REGENCY - A Magfirah Putri Zakiyah; Mardhatillah; Devy Febrianti; Sunandar Said (JTH: Journal of Technology and Health, 2026)
Employee performance serves as a key measure of organizational effectiveness and the achievement of institutional objectives, especially in health services. Even though national labor productivity has risen in recent years, that improvement does not necessarily indicate that every regional health agency has reached optimal performance. This research assessed the relationships between workplace conditions, work motivation, and employee performance at the Health Office of Sidenreng Rappang Regency. The study applied a quantitative, descriptive-analytic approach with a cross-sectional design. All 84 civil servants and government contract employees in the institution formed the population, and every member was selected through total sampling. Information was gathered with a Likert-scale questionnaire and examined using Chi-square analysis and binary logistic regression. Work environment and work motivation were each significantly related to employee performance (p < 0.05). In the multivariable analysis, the work environment produced the greatest statistical contribution (Wald = 13.927, p < 0.001), followed by work motivation (Wald = 6.741, p = 0.009). The results suggest that better physical and non-physical workplace conditions, accompanied by stronger employee motivation, may improve performance and support more dependable public health services.